Differentiall sandwich theorems for multivalent analytic functions associated with the Dziok-Srivastava operator (Tamsui Oxford Journal of Mathematical Sciences)
Dierential subordination and superordination results are obtained for multivalent analytic functions in the open unit disk that are as- sociated with the Dziok-Srivastava linear operator. These results are obtained by investigating appropriate classes of admissible functions. Sandwich-type results are also obtained.